Nepali Educational Grammar: Theory and Practice - Mandal, Ramdeo (Orchid Academia Siraha, 2022)
Although efforts are being made by domestic and foreign writers, it lacks standard level wise Nepali grammar. Therefore, the main goal of it is to develop standard level wise Nepali grammar by keeping standard grammatical contents regarding level. Primary and secondary sources were used to collect data, and qualitative analysis was performed through library work, comparative method and descriptive method. In various grammar studies alphabets, letters, syllable structure, word class, gender, number, person, tense, aspect, sense, voice, negative and positive, vocabulary, sentence difference, spelling, causative verb, idioms and definitional words are included. There is no clear boundary for grammar in different levels such as lower secondary Nepali grammar. Secondary Nepali grammar and expression, compulsory Nepali for proficiency level, higher secondary Nepali grammar and expression, and graduate level (301). It seems there is uncertainty rather than uniformity during teaching-learning. Therefore, particularly Nepali grammar should be developed to get rid of such situation and to compensate its lack.